PERCEPTIONS OF HEALTH PROFESSIONALS ON CONCEPTS CLINICAL ECONOMICS AND PATIENT ADVOCATE - Silva Sobrinho, Reinaldo Antonio da; Baggio, Maria Aparecida; Zilly, Adriana; Colombelli, Fabiana; Porzsolt, Franz (Revista Baiana de Enfermagem‏, 2022)
Objective: to understand the perspective of health professionals on the concepts of Clinical Economics and Patient Advocate. Method: a qualitative study with health professionals. Data were collected in June/2017 from the question: What is your perception of the concept of Clinical Economics and Patient Advocate? Qualitative data were analyzed using the Collective Subject Discourse. Results: the speeches pointed out that it deals with innovative, challenging and applicable proposals for nursing and health care. Patient Advocate and the Clinical Economics concept can support the decisions of the health team/service managers. The ideas can enhance the integration of the teams, resolve conflicts, bring together different professional categories and mitigate the risks of legal, financial and ethical responsibilities regarding health care. Conclusion: the concepts was understood as fundamental and applicable, since the organization survive with adequate human, financial and material management. Descriptors: Nursing. Patient safety. Health economics. Patient care team.